PENINGKATAN PEMBERIAN ASI EKSKLUSIF MELALUI BOOKLET BREASTFEEDING SELF -EFFICACY - hartati, suryani; Silitonga, Junita (Poltekkes Kemenkes Bengkulu, 2023)
Exclusive breastfeeding can be given successfully if the mother has self-confidence or Breastfeeding self-efficacy (BSE) and increase if the mother is given health education using media in the form of booklets. The aim of the study was to determine whether there was an increase in exclusive breastfeeding through a breastfeeding self-efficacy booklet given from prenatal to postnatal. The method used is quantitative with a quasi-experimental design. This design uses the instrument Breastfeeding self-efficacy scale short form (BSES-SF ) pre and post test in the sample group, as a measure of mothers' beliefs in BSES-SF consisting of 14 statement points which are responded to with a Likert scale ranging from 1 to 5 Breastfeeding Self- Efficacy Scale (BSES) developed by Dennis & Faux (1996). The time of the study started in October 2021 and was repeated in January 2022. The results of this study found that there was a significant increase in knowledge about exclusive breastfeeding, an average of 60.97. Result pvalue: 0.000 (pvalue <0.05). Suggestions for nurses can convince mothers to be able to provide exclusive breastfeeding through health education the use media booklet Brestfeeding self-efficacy (BSE). Keyword : Brestfeeding self-efficacy (BSE), ASI eksklusif, Booklet ABSTRAK Pemberian ASI Eksklusif dapat berhasil diberikan jika ibu memiliki keyakinan diri / Brestfeeding self-efficacy (BSE) dan meningkat bila ibu diberikan pendidikan kesehatan dengan menggunakan media berupa booklet. Tujuan penelitian untuk mengetahui adanya peningkatan pemberian ASI eksklusif melalui booklet breasfeeding self-efficacy yang diberikan sejak prenatal sampai dengan post natal. Metode yang digunakan adalah kuantitatif dengan desain quasi eksperimen. Desain ini menggunakan instrumen Breastfeeding self- efficacy scale short form (BSES-SF )pre dan post test pada kelompok sampel, sebagai alat ukur keyakinan ibu dalam BSES-SF terdiri dari 14 poin pernyataan yang direspon dengan skala likert rentang 1 sampai 5 Breastfeeding Self- Efficacy Scale (BSES) yang dikembangkan oleh Dennis & Faux (1996). Waktu penelitian dimulai dari bulan Oktober 2021 dan diulang pada Januari 2022. Hasil penelitian ini ditemukan adanya peningkatan pengetahuan yang signifikan tentang pemberian ASI eksklusif rerata sebesar 60,97. Hasil pvalue : 0,000 (pvalue<0,05).Kesimpulan perawat dapat menyakini ibu untuk dapat memberikan ASI eksklusif melalui pendidikan kesehatan dengan menggunakan media booklet Brestfeeding self-efficacy (BSE). Kata kunci : Brestfeeding self-efficacy (BSE), ASI eksklusif, Booklet